Effects of in situ dual ion beam (He+ and D+) irradiation with simultaneous pulsed heat loading on surface morphology evolution of tungsten–tantalum alloys. (22nd December 2017) - Gonderman, S.; Tripathi, J.K.; Sinclair, G.; Novakowski, T.J.; Sizyuk, T.; Hassanein, A.
Abstract: The strong thermal and mechanical properties of tungsten (W) are well suited for the harsh fusion environment. However, increasing interest in using tungsten as plasma-facing components (PFCs) has revealed several key issues. These potential roadblocks necessitate more investigation of W and other alternative W based materials exposed to realistic fusion conditions. In this work, W and tungsten–tantalum (W–Ta) alloys were exposed to single (He + ) and dual (He +   +  D + ) ion irradiations with simultaneous pulsed heat loading to elucidate PFCs response under more realistic conditions. Laser only exposer revealed significantly more damage in W–Ta samples as compared to pure W samples. This was due to the difference in the mechanical properties of the two different materials. Further erosion studies were conducted to evaluate the material degradation due to transient heat loading in both the presence and absence of He + and/or D + ions. We concluded that erosion of PFC materials was significantly enhanced due to the presence of ion irradiation. This is important as it demonstrates that there are key synergistic effects resulting from more realistic fusion loading conditions that need to be considered when evaluating the response of plasma facing materials.